Efficacy analysis of rituximab in treating patients with primary membranous nephropathy dependent on calcineurin inhibitors - Li, Zhuo; Zhao, Tingting; Zhang, Shasha; Huang, Jing; Wang, Honggang; Sun, Yujiao; Wang, Rong; Chen, Bing (Frontiers in Immunology, 2024)
BackgroundThis study evaluated the efficacy of rituximab (RTX) in primary membranous nephropathy (PMN) patients with incomplete remission and drug dependence after long-term use of calmodulin inhibitors (CNIs). It aims for complete clinical and immunological remission, and cessation of CNI dependence.MethodsThirty-six patients were enrolled in the study with two groups: drug-dependent and partial remission or immune non-remission group. Both groups underwent RTX therapy with gradual CNI tapering to end CNI dependency and induce complete remission. The primary outcome was overcoming CNI dependency and achieving complete remission after 12 months of RTX therapy. Secondary outcomes included immunological remission and recurrence rates.ResultsThe drug-dependent group (20 patients) achieved significant proteinuria reduction compared to the partial remission or immune non-remission group (16 patients) (P=0.016). After 12 months of RTX treatment, all drug-dependent patients overcame CNI dependency (average withdrawal period: 5.3 ± 3.7 months), with complete remission rates increased from 10% to 70.0% and complete immunological remission rates rose from 35.0% to 90.0%. In the partial remission or immune non-remission group, 14 patients discontinued CNI (average period: 4.6 ± 4.5 months), with complete remission rates increasing from 5.0% to 68.8% and complete immunological remission rates from 6.3% to 68.8%. During follow-up, serum albumin increased, and anti-PLA2R antibodies, 24-hour proteinuria, and CD19+ cell numbers reduced, while creatinine remained stable. Three patients relapsed, four encountered adverse events, and no malignancies or other fatal adverse events were reported.ConclusionsRTX effectively achieves complete clinical and immunological remission in PMN patients dependent on or partially responsive to long-term CNI therapy, reducing recurrence and minimizing prolonged immunosuppressive therapy risks.